Acute spinal cord compression: a rare complication of dual antiplatelet therapy. (22nd July 2015) - Iskandar, Muhammad Zaid; Chong, Victor; Hutcheon, Stuart
Abstract : A 73-year-old woman presented with acute shortness of breath and exacerbation of chronic back pain. She was diagnosed with pulmonary oedema and a non-ST-elevation myocardial infarction following chest X-ray, ECG and high sensitivity troponin levels. She subsequently underwent coronary angioplasty with deployment of drug-eluting stents to her circumflex and left anterior descending arteries and was started on aspirin and clopidogrel for her dual antiplatelet therapy. Unfortunately, following the procedure, she gradually lost power and sensation in both lower limbs. MRI of her spine confirmed an extradural haematoma causing thoracic cord compression. She was managed conservatively following discussions with neurosurgeons and developed further complications secondary to her immobility.